PENGARUH PENGGUNAAN TEPUNG DAUN KELOR (MORINGA OLEIFERA) DAN MINYAK KELAPA SAWIT TERHADAP KONSUMSI PROTEIN DAN RETENSI NITROGEN PAKAN DOMBA - Qurozi, Abdullah; Suryapratama, Wardhana; Munasik, Munasik (ANGON: Journal of Animal Science and Technology, 2021)
Background. The purpose of the study was to examine the effect of giving Moringa leaf flour and palm oil on protein consumption and nitrogen retention of lamb diet. Materials and methods. The research was carried out on 27 June 2020 to 27 September 2020, at the Experimental Farm and Nutrition and Animal Feed Science Laboratory, Faculty of Animal Sciene, Jenderal Soedirman University, Purwokerto. The research material used were 18 males thin tailed lamb, aged 7-8 months, the average body weight 18,9 ± 1,9 kg. The feed used were 40% napier grass silage base and 60% concentrate (2 parts of rice bran and 1 part of coconut meal). The supplementary feed given are Moringa leaf flour and palm oil. The study used an in vivo experimental method with a Completely Randomized Design (CRD), 3 treatments and 6 replications. The treatments given was R0 = control feed (40% grass silage + 60% concentrate); R1 = R0 + Moringa leaf flour (2% DM feed); and R2 = R1 + palm oil 0.5% of feed. The variables measured were protein consumption and nitrogen retention of lamb diet. Results. The results showed the of protein consumption at R0= 86.08 ± 8.20; R1= 129.54 ± 18.28; and R2= 109.76 ± 13.60. Average nitrogen retention at R0= 9.63 ± 3.00; R1= 15.99 ± 3.83; dan R2= 13.08 ± 2.02. The results of the analysis showed that the use of Moringa leaf flour (Moringa oleifera) 2% DM feed and palm oil of lamb diet had a very significant effect on lamb protein consumption and a very significant effect on lamb nitrogen retention. Conclusion. The conclusion of the study is the treatment Moringa leaf flour (Moringa oleifera) was able to increase lamb protein onsumption by 50.48%, nitrogen retention in lamb by 66.04%.